1, 3-Dipolar cycloaddition reactions between ethyl diazoacetate and substituted alkynes: A density functional theory study. (1st September 2014) - Tajabadi, Javad; Bakavoli, Mehdi; Gholizadeh, Mostafa; Eshghi, Hossein; Khojastehnezhad, Amir
A theoretical study on the reactivity and regioselectivity of 1, 3-dipolar cycloaddition reactions of ethyl diazoacetate (EDA) with ethynes (CH ≡ CX, X = H, CH3, n-But, CF3, CO2Et, C6H5, p-CH3OC6H4 and p-NO2C6H4) has been carried out by means of several theoretical approaches, activation energies, frontier molecular orbital (FMO) theory, conceptual density functional theory reactivity indices and hard and soft acid and base theory. Potential energy surface analysis and intrinsic reaction coordinate calculations show that these cycloadditions follow an asynchronous concerted mechanism with a low or non-polar character, displaying C-regioselectivity. Moreover, the reaction of EDA with electron-deficient alkynes is faster compare to electron-rich ethynes. Reactions of EDA with electron-deficient and electron-rich alkynes are normal electron demand and inverse electron demand cycloadditions, respectively, because of moderate electrophilicity and nucleophilicity of EDA. This result is confirmed by FMO analysis and reactivity indices.